An Investigative Study on Attitudes and Perceptions of Hypertensive Clients at Queen Elizabeth Central Hospital - Chiumia, Taweni (Kamuzu University of Health Sciences, 2022)
This qualitative study is aimed at describing the attitudes and perceptions of hypertensive clients towards treatment non-compliance. The study will therefore help explore the exact cause of treatment non- compliance among hypertensive clients. The specific objectives of the study are : to find out hypertensive clients' attitudes towards treatment of hypertension; to find out if hypertensive clients knowledge about the importance of treatment compliance; to identify problems that influence clients to treatment non- compliance and to find out the perceived patient related factors with self reported non-compliance of antihypertensive treatment. This descriptive methodology has been used because it utilizes methods of enquiry that emphasize subjectivity and the meaning of the experience to the individual presented in thoughts, ideas, feelings, attitudes and perceptions. A sample of 20 hypertensive clients will be recruited through purposeful sampling methods. Data will be collected using interviews using q interview guides in form of questionnaires designed by the researcher. Data will be analyzed manually and will be interpreted and illustrated using figures (expressed in percentages), graphs, tables and diagrams. The results will be used in enhancing the reduction of the higher morbidity and mortality rates that come due to hypertension crisis since the study will enable finding out the actual cause of treatment noncompliance.